Faith, Trust, and Technology: Conceptual Insights into Sharia Financial Literacy and Digital Security in Islamic Fintech - Neng Cahya; Mohamad Anton Athoillah (Islamicate Institute, 2026)
The rapid development of Islamic financial technology (Sharia Fintech) presents new opportunities and challenges in combining faith-based principles with digital innovation. This conceptual paper explores the intersection between Sharia financial literacy and digital security perception as key dimensions shaping user trust in Islamic fintech ecosystems. Drawing on Islamic ethical frameworks and technology acceptance theories, this study argues that faith-oriented literacy and perceptions of security co-construct the moral and psychological foundations of user confidence in Sharia-compliant digital platforms. The paper proposes a conceptual linkage where faith serves as the moral compass, trust as the mediating psychological mechanism, and technology as the enabler of financial inclusion. The insights presented aim to contribute to theoretical discussions on ethical digital finance and provide a foundation for future empirical research in the field of Islamic fintech.